Livelihood Patterns of the Tibetan Refugees in Kathmandu - Shahi, Neelam (KMC Research Journal, 2018)
This Study entitled as “Livelihood Pattern of the Tibetan Refugees in Nepal” (A Case Study of the Samdupling in Jawalakhel and Khampa Refugee Camp in Boudha- Jorpati) aims to discover the livelihood patterns of Tibetan refugees residing in the Samdupling camp in Jawalakhel and Khampa Refugee’s Camp in Boudha-Jorpati. The paper intends to examine the problems confronted by Tibetan refugees residing in the Samdupling camp and Khampa Refugee’s Camp. The study itself is conducted with the objectives of describing the present socio-economic status of Tibetan refugees dwelling in aforementioned camps located inside the Kathmandu valley and Lalitpur. This write-up not only deals with different livelihood aspects of Tibetan refugees but also compares the livelihood of two camps to list out the social, economic and political problems affecting their livelihood. However, this study is mainly based on the primary information and the data which were collected using the techniques of household survey and sampling survey, along with questionnaire and interview during the several field visits to camps. The paper concludes by stating that government intervention is required to resolve the issues affecting the livelihood of Tibetan refugees. Tibetan refugees’ problems required a political yet humanitarian resolution. The government needs to decide on whether to endow the citizenship or refugee card to the refugees who have been deprived of the both, or opt for the third-party settlement. For that Tibetans refugees also need to cooperate and coordinate with the refugees department under the Ministry of the Home Affair, Government of Nepal